Myxofibrosarcoma of the Male Breast – an Infrequent Neoplasm: a Case Report and Comprehensive Review - Shagufta Qadri (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Primary breast sarcoma is a rare type of malignancy arising from the mesenchymal tissue of the breast and represent less than 1% of all breast cancers. We report a rare case of myxofibrosarcoma in a 25 year old male patient, who presented with rapidly enlarging mass, in his right breast extending upto right axilla since 5 month, the patient also had history of right breast lumpectomy 2 years back. On the basis of history, clinical examination and fine needle aspiration cytology a provisional diagnosis of stromal sarcoma breast with myxoid change was made. However histopathological examination and the immunohistochemical analysis lead to a conclusive diagnosis of myxofibrosarcoma breast with local recurrence. Myxofibrosarcoma shows a predilection for multiple local recurrences, tendency of low-grade tumour to recur at higher grades and potential metastasis which emphasizes the need for accurate diagnosis and excision in specialized centres.